Scope of income independence of local self-governments situation of Western Pomeranian local self-government units in the nationwide comparison - Magdalena Kogut-Jaworska (Ekonomiczne Problemy Usług, 2015)
Scope and importance of income independence of territorial self-government units  determines to a large extent their opportunities of development, as well as their real  possibilities to meet existing challenges. Income independence of local governments should, by definition, denote independence of local communities in establishing income sources for the local budget. Assessing the level of income independence is crucial in order to measure the actual scope of financial decisions which can be taken by self-government units. The aim of the paper is to assess the scope of income independence of local self-governments in Western Pomerania and to compare it with local self-governments in the other regions of Poland.